DYTOGENETIC ANALYSIS OF HELA AND CHANG CELLS - N.Lzadian; H.Sussman (Tehran University of Medical Sciences, 1982)
Based on the evaluation of two human cell lines, Hela and Chang, abeuploidy and several marker chromosomes were found in both cells. The morphological characteristic of marker chromosomes of Chang cells was distinctly different from HeLa. Certain submetacentric marker chromosome was frequently present among 80% of marker chromosomes of Chang cells which distinguished this line from HeLa, which showed the various identifiable marker chromosomes. This evidence clearly established the different etiology of these two human cell lines.